Study on the Potential of Forest Areas in Aspects of Land Fertility In Wonosalam District, Jombang Regency - Maroeto; Rossyda Priyadarshini; Siswanto; Mohammad Idhom; Wahyu Santoso (Future Science, 2021)
Forests are one of the natural resources of high value for human benefit, both direct and indirect benefits. The management of forest resources does not date from the legal basis of Article 6 of Law no. 41 of 1999 (regarding Forestry) which states that natural resource management efforts in forest areas are carried out through protection, conservation and production functions by taking into account the continuity of their supply and the surrounding environment. UPN